Energy impacts : a multidisciplinary exploration of North American energy development : synthesis across the social sciences - Jacquet, Jeffrey B. (Jeffrey Bryan), 1979-; Haggerty, Julia H. (Julia Hobson); Theodori, Gene Louis (Society and natural resources book series., 2021)
"Bringing important new research on site-level social, economic, and behavioral impacts from large-scale energy development. Featuring conceptual and empirical research from leading social scientists and compares, synthesizes, bridges, and traverses constraints on the coordination of energy impacts research, creating a new opportunity to understand North America's future energy needs"--